PROGESTERONE, METABOLITES AND MINERALS IN ANESTRUS, SUBESTRUS, REPEAT BREEDING AND CYCLIC COWS - KUMAR, RAJESH; BUTANI, M G; DHAMI, A J; KAVANI, F S; PATEL, M D; SHAH, R J (The Indian Journal of Animal Reproduction, 2023)
A comparative field study on serum profile of progesterone (p4) and metabolites of 21 anestrus,10 subestrus, 31 repeat breeding and 8 normal cyclic crossbred cows revealed that the serum P4 was significantly (P
Keywords: Blood profile; Cows; Anestrus; Subestrus; Repeat breeders; Normal cyclic